Zinc ion increases the effectiveness of phosphorus in agricultural soils through microbial solubilization - Lanxin Tang; Bingrui Su; Xuehao Zheng (PLoS ONE, 2025)
Phosphorus (P) is a key limiting factor for crop growth in agroecosystems, where soil microorganisms and mineral ions are essential for P turnover and mobilization. However, it is unclear how mineral ions affect microbially-mediated phosphorus cycling. In this study, 15 soil samples were collected from a typical agricultural area in Southwest China with a complex mineral composition. Soil phosphorus levels, microbial phosphorus genes, and typical soil mineral ions were subsequently analyzed to determine the mechanism of soil mineral ions on phosphorus cycling. The results showed that Zn 2+ was the main driver of P mobilization in the soils, and its accumulation led to changes in the expression of two important phosphorus genes, gcd and phnW . Ecological clusters dominated by Actinobacteria and Proteobacteria, phyla that carry the gcd gene, directly contributed to P activation through mutualistic interactions. phnW encodes a phosphorylglycolide hydrolase enzyme involved in phosphate accumulation, and its transcription may enhance the soil available phosphorus (AP) content by promoting enzymatic carbon-phosphorus bond cleavage, a process influenced by microbes in the phyla Proteobacteria, Gemmatimonadetes, Actinobacteria, and Acidobacteria. Herein, our work provides a new perspective on the mechanism of P cycling and improve P effectiveness in agricultural soils.